Multifrequency STD NMR Unveils the Interactions of Antibiotics With Burkholderia multivorans Biofilm Exopolysaccharide - Nepravishta, Ridvan; Monaco, Serena; Distefano, Marco; Rizzo, Roberto; Cescutti, Paola; Angulo, Jesus (Frontiers in Molecular Biosciences, 2021)
Biofilms confine bacterial cells within self-produced matrices, offering advantages like protection from antibiotics, entrapment of nutrients, etc. Polysaccharides are major components in these macromolecular assemblies, and their interactions with other chemicals are of high relevance for the benefits provided by the biofilm 3D molecular matrix. NMR is a powerful technique for the study and characterization of the interactions between molecules of biological relevance. In this work we have applied multifrequency-saturation transfer difference (STD) NMR and DOSY NMR approaches to elucidate the interactions between the exopolysaccharide produced by Burkholderia multivorans C1576 (EpolC1576) and the antibiotics Kanamycin and Ceftadizime. The NMR strategies presented here allowed an extensive characterization at atomic level of the mechanisms behind the implication of the EpolC1576 in the recalcitrance phenomena, which is the ability of bacteria in biofilms to survive in the presence of antibiotics. Our results suggest an active role for EpolC1576 in the recalcitrance mechanisms toward Kanamycin and Ceftadizime, though through two different mechanisms.